2011
DOI: 10.1371/journal.pone.0023252
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Elimination of MHC-I-Deficient Lymphocytes by Activated Natural Killer Cells Is Independent of Granzymes A and B

Abstract: NK cells kill target cells mainly via exocytosis of granules containing perforin (perf) and granzymes (gzm). In vitro, gzm delivery into the target cell cytosol results in apoptosis, and induction of apoptosis is severely impaired in the absence of gzm A and B. However, their importance for in vivo cytotoxicity by cytotoxic T cells has been questioned. We used an in vivo NK cytotoxicity assay, in which splenocytes from wild-type and β2microglobulin-deficient (MHC-Ineg) mice are co-injected into recipients whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The most abundantly released Gzm at the site of the immunological synapse are GzmA and GzmB, which in vitro are proapoptotic molecules. While questions remain on the requirement of Gzm for NK‐cell and T‐cell‐mediated in vivo cytotoxicity , the Gzms also possess noncytolytic activities that can contribute to inactivation of intracellular pathogens (reviewed in ). The Fas receptor (Fas or CD95) is a transmembrane protein expressed on all nucleated cells, and induces apoptosis upon engagement of Fas ligand expressed on cytotoxic effector cells.…”
Section: Introductionmentioning
confidence: 99%
“…The most abundantly released Gzm at the site of the immunological synapse are GzmA and GzmB, which in vitro are proapoptotic molecules. While questions remain on the requirement of Gzm for NK‐cell and T‐cell‐mediated in vivo cytotoxicity , the Gzms also possess noncytolytic activities that can contribute to inactivation of intracellular pathogens (reviewed in ). The Fas receptor (Fas or CD95) is a transmembrane protein expressed on all nucleated cells, and induces apoptosis upon engagement of Fas ligand expressed on cytotoxic effector cells.…”
Section: Introductionmentioning
confidence: 99%
“…We show herein that this mouse strain is on a mixed 6J/6N background and contains full length Nnt, with the NNT protein involved in ROS regulation. For example, T cell activities can be regulated by ROS in a range of settings (Chen et al, 2016;Franchina et al, 2018;Murphy and Siegel, 2013;Yarosz and Chang, 2018), perhaps contributing to the controversy (Ebnet et al, 1995;Joeckel and Bird, 2014;Regner et al, 2009;Regner et al, 2011;Smyth et al, 2003) regarding the role of lymphocyte-derived GzmA as a mediator of cellular cytotoxicity (Pardo et al, 2002;Pardo et al, 2004;Shresta et al, 1999;Susanto et al, 2013). Whether all the pheontypes reported for GzmA -/mice were compromised by Nnt (or mixed the background) remains unclear and may require new experiments to resolve, similar to those described herein for CHIKV arthritis.…”
Section: Discussionmentioning
confidence: 77%
“…For instance, control of viral infections can be compromised in GzmA -/mice (Loh et al, 2004;Mullbacher et al, 1996;Pereira et al, 2000;Riera et al, 2000), with cytotoxic lymphocytes from these mice reported to be less able to kill target cells (Pardo et al, 2002;Pardo et al, 2004;Shresta et al, 1999;Susanto et al, 2013). Like granzyme B (GzmB), GzmA has thus been classified as a cytotoxic granzyme (Golstein and Griffiths, 2018;Mpande et al, 2018;Muraro et al, 2017;Zhou et al, 2020), although in several studies a role for GzmA in mediating cellular cytotoxicity was not observed (Ebnet et al, 1995;Joeckel and Bird, 2014;Regner et al, 2009;Regner et al, 2011;Smyth et al, 2003). In a range of settings GzmA has also been associated with the promotion of inflammation, providing an additional or alternative view of its physiological role, although consensus on mechanisms has remained elusive (Metkar et al, 2008;Park et al, 2020;Santiago et al, 2020;Santiago et al, 2017;Schanoski et al, 2019;Shimizu et al, 2019; van Daalen et al, 2020;Wensink et al, 2015;Wilson et al, 2017), with a number of potential intracellular and extracellular targets for GzmA reported.…”
Section: Introductionmentioning
confidence: 99%
“…To determine if the alterations in NK Ly49 repertoire correlated with NK cell killing ability, we analyzed Sostdc1 -/- NK cell cytotoxicity with novel FCM-based in vivo and in vitro killing assays ( Figure 2 and Supplemental Figure 3A-3E ). Beta-2 microglobulin knockout (β 2 m -/- ) cells express little to no cell surface class I major histocompatibility complex (MHC I) molecules and therefore are sensitive targets for NK cell killing 28 . To test NK cell killing in vivo , we pre-activated NK cells in Sostdc1 -/- and WT control mice with poly(I:C) 29 (Figure 2A) and challenged them with equal numbers of β 2 m -/- and beta-2 microglobulin-sufficient (β 2 m +/+ ) target cells, each labeled with two different fluorochromes ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%